2012
DOI: 10.1017/s0031182011002423
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasite proteomics: from experimental models to human infections

Abstract: SUMMARYSchistosomiasis is a major human helminth infection endemic in developing countries. Urogenital schistosomiasis, caused by S. haematobium, is the most prevalent human schistosome disease in sub-Saharan Africa. Currently control of schistosome infection is by treatment of infected people with the anthelmintic drug praziquantel, but there are calls for continued efforts to develop a vaccine against the parasites. In order for successful vaccine development, it is necessary to understand the biology and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Despite the clear role of soluble egg proteins in the development of granulomas and a carcinogenic environment, the protein composition of this or other S . haematobium tissues/organs has not been fully characterised, although a few studies have identified several immunogenic proteins [21]. In contrast, different proteomes from the related species S .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clear role of soluble egg proteins in the development of granulomas and a carcinogenic environment, the protein composition of this or other S . haematobium tissues/organs has not been fully characterised, although a few studies have identified several immunogenic proteins [21]. In contrast, different proteomes from the related species S .…”
Section: Introductionmentioning
confidence: 99%
“…The public health significance of CE has stimulated a sustained period of investigation of immunity to E. granulosus , particularly in sheep which are the most common intermediate host involved in transmission of the parasite [ 20 ]. Immunization of livestock intermediate host animals could have an important effect in control of the disease both from an economic aspect and also their significant contribution in canine infections and so to accidental infections of human [ 1 , 3 , 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment of schistosomiasis alone is not enough to manage the disease; there is also a need for enhanced proteomic research that focuses on identifying vaccine candidates. Proteomic vaccine candidate studies try to identify antigens that normally stimulate a protective immune response (Mutapi, 2012). A recent focus of research is the potential use of a combination of antigens as vaccine candidates, which may be more effective than a single recombinant antigen vaccine (Ludolf et al, 2014).…”
Section: Diagnostics Drugs and Vaccinesmentioning
confidence: 99%
“…Another advantage of proteomic studies is that it gives information about differences in post-translational modifications (PTMs) (Mutapi, 2012). For example, multiple protein spots were found to be present on electrophoreses gels for the same protein in soluble egg antigen (SEA) samples of S. mansoni (Mathieson and Wilson, 2010), in ESP of F. hepatica (Jefferies et al, 2001) and in S. japonicum (Zhong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%